Mechanisms behind hazard perception of warning signs: An EEG study. (February 2020) - Zhu, Longfei; Ma, Qingguo; Bai, Xiaoxu; Hu, Linfeng
Abstract: Warning signs are the most effective way to alert people to hazards in the industries, architecture, and transportation. To better understand how these warning signs prompted hazard, this study investigated the intrinsic mechanism of hazard perception of warning signs, including warning words (low versus high hazard levels) and surrounding shapes (upright triangle versus circle). We recruited 18 participants and recorded electroencephalogram (EEG). We found that a combination of high-hazard-level words and an upright triangle shape significantly elicited more negative N300 and increased theta-band (3–8 Hz) synchronization, but reduced beta-band (15–30 Hz) desynchronization. The N300 component represented the emotional arousal strength, theta oscillations reflected the engagement of retrieval of emotional experiences from episodic memory, and beta oscillation connoted the semantic encoding. Thus, these findings suggested that a high-hazard-level combination had the ability to obtain high priority in cognitive processing. The EEG pattern changes allowed us to assess whether the hazard perception of warning signs was high or low, which could be an accurate indicator to better evaluate the design of warning signs.